Long-term outcomes of induction chemotherapy followed by concurrent chemoradiotherapy and adjuvant chemotherapy for locoregionally advanced nasopharyngeal carcinoma: a retrospective study - Zhao, Xiaoyan; Tian, Ling; Chen, Yun; Yang, Qing; Xie, Tao; Chen, Modong; Rao, Jinhui; Yang, Meng; Huang, Ning; Ren, Yanxin (Frontiers in Oncology, 2024)
BackgroundNasopharyngeal carcinoma (NPC) is a prevalent form of head and neck cancer, particularly in specific regions with a higher incidence. The optimal treatment strategy for locally advanced NPC (stage III and IVA, LA-NPC) involves various combinations of induction chemotherapy (IC), concurrent chemoradiotherapy (CCRT), and adjuvant chemotherapy (AC), each with distinct advantages. This one institutional study aims to retrospectively analysis the efficacy and clinical outcomes of IC with CCRT (IC+CCRT), CCRT with AC (CCRT+AC), and the comprehensive approach of IC followed by CCRT and subsequently AC (IC+CCRT+AC) in the management of LA-NPC.Materials and methodsA total of 352 LA-NPC patients were included: 173 accepted IC+CCRT, 60 received CCRT+AC, and 119 underwent IC+CCRT+AC. The primary endpoints including overall survival (OS) and progression-free survival (PFS), were assessed using the Kaplan-Meier method and log-rank test.ResultsThe median follow-up was 61.2 months (1-216 months). There was no significant difference in 5-year OS and PFS between IC group and no IC group, extending the observation time to 90 months, the OS and PFS were significantly better in IC group than no IC group (OS: 76% vs. 70%,P<0.05; PFS: 76% vs. 71%, P<0.05). Patients with 1, 2, or 3 cycles of IC had higher 5-year OS and PFS than those with more than 3 cycles (1-4 cycles IC OS: 89% vs. 87% vs. 88% vs. 79%, P<0.05; 1-4 cycles IC PFS: 87% vs. 85% vs. 85% vs. 70%, P<0.05). NP regimen demonstrated higher OS and PFS than TP, PF, and TPF regimens (OS: 95% vs. 82% vs. 85% vs. 71%, P<0.05; PFS: 93% vs. 83% vs. 81% vs. 80%, P<0.05). The 5-year OS and PFS were significantly better in AC group than no AC group (OS: 82% vs. 72%, P<0.05; PFS: 81% vs. 69%, P<0.05). In the AC group, there was no differential effect of chemotherapy cycles and chemotherapy regimens on patients’ OS and PFS. In the ThNh group, patients receiving IC+CCRT+AC had higher OS and PFS compared to those receiving IC+CCRT, with no significant difference in the rest (OS: 85% VS 66% P<0.05; PFS: 78% VS 62%, P<0.05).ConclusionCCRT combined with IC or AC could benefit LA-NPC patients. The IC+CCRT +AC regimen was most beneficial for NPC patients with later T and N stages.